2007
DOI: 10.1002/adfm.200600439
|View full text |Cite
|
Sign up to set email alerts
|

Microdroplet and Atomic Force Microscopy Probe Assisted Formation of Acidic Thin Layers for Silicon Nanostructuring

Abstract: In this work, an aqueous acidic thin‐layer‐based strategy for fabricating nanostructures on silicon by using atomic force microscopy (AFM) nanolithography is presented. The approach involves the formation of microscale droplets via dilute hydrofluoride (DHF) etching, the conversion of the droplets to acidic thin layers by AFM‐probe scanning, and subsequent lithographic operations using a biased probe in the aqueous layers. By varying the concentration of the acidic DHF layers, the thin layers can facilitate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…At proper tip bias and pulse duration, negative nanostructures can be fabricated by field-assisted Si dissolution, just like the experiment performed in dilute hydrofluoride liquid thin layer. 29 That was the results observed under −8 0 V tip bias and 0.1 s pulse duration. When the pulse duration exceeds the threshold value, the silicon oxide produced by anodic oxidation in the later stage of the lithography process accumulates to form positive patterns after fluorine ions used up (longer pulse duration in Fig.…”
Section: Resultssupporting
confidence: 66%
“…At proper tip bias and pulse duration, negative nanostructures can be fabricated by field-assisted Si dissolution, just like the experiment performed in dilute hydrofluoride liquid thin layer. 29 That was the results observed under −8 0 V tip bias and 0.1 s pulse duration. When the pulse duration exceeds the threshold value, the silicon oxide produced by anodic oxidation in the later stage of the lithography process accumulates to form positive patterns after fluorine ions used up (longer pulse duration in Fig.…”
Section: Resultssupporting
confidence: 66%
“…The formation of negative patterns in Figure can be reasonably explained by the removal of the adsorbed HDT molecules with the application of negative bias since the gold−sulfur bond was broken in a cathodic process as has been proved in the bias-assisted nanolithography. , As for the big difference between the depth of the negative patterns and the thickness of HDT monolayers (∼2.06 nm), it may be attributed to the adsorption of unremoved HDT molecules and contaminants (from reaction residual or air) onto the fresh gold because of the high surface energy of such fresh gold and some extent deformation of the surrounding HDT SAMs under the load of the tip . Recently, Xie et al reported the formation of positive and negative nanopatterns on silicon first by formation of microscale droplets via dilute hydrofluoride etching, then conversion of the droplets to acidic thin layers by AFM probe scanning, and then subsequent fabrication using bias-assisted nanolithography in the aqueous layers . The process is not reversible.…”
Section: Resultsmentioning
confidence: 60%
“…7 Recently, Xie et al reported the formation of positive and negative nanopatterns on silicon first by formation of microscale droplets via dilute hydrofluoride etching, then conversion of the droplets to acidic thin layers by AFM probe scanning, and then subsequent fabrication using bias-assisted nanolithography in the aqueous layers. 17 The process is not reversible.…”
Section: Simultaneous Fabrication Of Positive and Negativementioning
confidence: 99%
“…Kinser et al performed anodic oxidation under organic solvents in order to tune the polarity of the surrounding liquid and thereby control the size of the meniscus [549,550]. Other solvents can also promote localized oxidation of a Si surface, such as dilute (0.05-1.0%) hydrofluoric acid (HF) [551,552]. Self-assembled monolayers have also been used as positive and negative tone resists for this SPL [553].…”
Section: Anodic Oxidationmentioning
confidence: 99%